Coagulation markers in diagnostic and monitoring of thromboembolic complication in COVID-19 - Czarnecka-Czapczyńska, Magdalena; Bartusik-Aebisher, Dorota; Krupka-Olek, Magdalena; Aebisher, David; Cieślar, Grzegorz; Latos, Wojciech; Kawczyk-Krupka, Aleksandra (European Journal of Clinical and Experimental Medicine, 2021)
<h2 class="block-title" style="box-sizing: border-box; font-family: Lato, sans-serif; font-weight: bold; line-height: 1.1; color: #010101; margin-top: 23px; margin-bottom: 11.5px; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; letter-spacing: 0.1px; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Abstract <div class="field-name-field-autorzy-" style="box-sizing: border-box; font-size: 14px; color: #010101; display: inline-block !important; float: left !important; padding: 10px 24px 0px 0px !important; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;"> Introduction. Coronavirus disease 2019 (COVID-19) was first observed in China in Wuhan city, Hubei province in December, 2019, and specified as a pandemic by the World Health Organization (WHO). COVID-19 is caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARSCoV2). Aim. The aim of this article is to discuss epidemiology of thromboembolic complication in COVID-19. Material and methods. This article is a review done in regards to discuss clinical features of the anticoagulation treatment in COVID-19. Analysis of the literature. A review is discussed an anticoagulation treatment in 41 manuscripts. Conclusion. Most commonly coagulation abnormalities in patient with COVID-19 is mild thrombocytopenia. Apart from their typical role in thrombosis and hemostasis, platelets mediate key aspects of immune and inflammatory.